2009
DOI: 10.1002/adma.200901515
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Brushes with Nanometer‐Scale Gradients

Abstract: Surfaces with steep height or composition gradients at the nanometer scale are synthesized from self‐asssembled photoinitiator monolayers. The monolayers are prestructured by interference lithography followed by brush growth. Through step‐and‐repeat processes, surfaces with nano meter‐scale composition gradients are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 45 publications
1
67
0
Order By: Relevance
“…36 They exploited the smooth continuous gradient of exposure available in an interferometer to yield a well-defined gradient of brush grafting density. They utilized a photoinitiator to polymerize acrylamide, while we have employed a halogen initiator for ATRP.…”
Section: E Nanofabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…36 They exploited the smooth continuous gradient of exposure available in an interferometer to yield a well-defined gradient of brush grafting density. They utilized a photoinitiator to polymerize acrylamide, while we have employed a halogen initiator for ATRP.…”
Section: E Nanofabricationmentioning
confidence: 99%
“…38,39 Schuh et al fabricated gradients, consisting of a continuously varying density of brushes, by using an interferometer to degrade a photoinitiator-functionalized surface. 36 In the present work, we explore a rapid simple approach to brush patterning based on the dehalogenation of a bromoor chlorofunctionalized surface. Previously it has been reported that benzyl chloride terminated siloxane films may be dehalogenated by exposure to UV light.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…77 This technique was proved useful for the quantification of surface forces for various soft matter systems. 55,78,79 The colloidal particle attached to the tip was a silica sphere with a radius of 500 nm. Typical raw data showing the approach section of deflection vs piezo-extension curves for the PNIPAM grafts are shown in Figure 3.8.…”
Section: Afm Force Measurements On Mb Pnipam Graftsmentioning
confidence: 99%
“…due to the precise control of physical and chemical surface properties, and so on. 79 Nanopatterned polymer grafts with defined features become especially interesting when the pattern dimensions are close to the length of the grafted macromolecules. [80][81][82] AFM-based techniques, such as nanoscratching, 83,84 dip-pen nanolithography (DPN) [85][86][87] and scanning probe oxidation (SPO) [88][89][90] offer versatile patterning techniques across the length scales.…”
mentioning
confidence: 99%